Mutant Huntingtin Fails to Directly Impair Brain Mitochondria - Hamilton, James (J Neurochem, 2019)
Although the mechanisms by which mutant huntingtin (mHtt) results in Huntington’s disease (HD) remain unclear, mHtt-induced mitochondrial defects were implicated in HD pathogenesis. The effect of mHtt could be mediated by transcriptional alterations, by direct interaction with mitochondria, or by both. In the present study, we tested a hypothesis that mHtt directly damages mitochondria. To test this hypothesis, we applied brain cytosolic fraction from YAC128 mice, containing mHtt, to brain nonsynaptic and synaptic mitochondria from wild-type (WT) mice and assessed mitochondrial respiration with a Clark-type oxygen electrode, membrane potential and Ca(2+) uptake capacity with tetraphenylphosphonium (TPP(+))- and Ca(2+)-sensitive electrodes, respectively, and, ROS production with Amplex Red assay. The amount of mHtt bound to mitochondria following incubation with mHtt-containing cytosolic fraction was greater than the amount of mHtt bound to brain mitochondria isolated from YAC128 mice. Despite mHtt binding to WT mitochondria, no abnormalities in mitochondrial functions were detected. This is consistent with our previous results demonstrating the lack of defects in brain mitochondria isolated from R6/2 and YAC128 mice. This, however, could be due to partial loss of mitochondrially bound mHtt during the isolation procedure. Consequently, we increased the amount of mitochondrially bound mHtt by incubating brain nonsynaptic and synaptic mitochondria isolated from YAC128 mice with mHtt-containing cytosolic fraction. Despite enrichment of YAC128 brain mitochondria with mHtt, mitochondrial functions (respiration, membrane potential, ROS production, Ca(2+) uptake capacity) remained unchanged. Overall, our results suggest that mHtt does not directly impair mitochondrial functions, arguing against the involvement of this mechanism in HD pathogenesis.